2015
DOI: 10.1002/bmc.3611
|View full text |Cite
|
Sign up to set email alerts
|

Influence of verapamil on pharmacokinetics of pristimerin in rats

Abstract: The aim of this study was to investigate the effects of verapamil on the pharmacokinetics of pristimerin in rats. A sensitive and reliable LC-MS/MS method was developed and applied for the determination of pristimerin in rat plasma. The pharmacokinetics of orally administered pristimerin with and without verapamil pretreatment was investigated. The results indicated that, when the rats were pretreated with verapamil, the peak concentration of pristimerin increased from 189.13 to 277.53 ng/mL (46.7%), and the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The complexes of CD and triterpenic acids were prepared according to several reported studies with minor modifications (Gao et al, 2016;Ren et al, 2016). In general, 30% β-CD (30 g β-CD dissolved in 100 mL water) was used for forming the inclusion complexes.…”
Section: β-Cd Inclusion Complexes Of Triterpenic Acidsmentioning
confidence: 99%
“…The complexes of CD and triterpenic acids were prepared according to several reported studies with minor modifications (Gao et al, 2016;Ren et al, 2016). In general, 30% β-CD (30 g β-CD dissolved in 100 mL water) was used for forming the inclusion complexes.…”
Section: β-Cd Inclusion Complexes Of Triterpenic Acidsmentioning
confidence: 99%
“…2015; Gao X et al. 2016). To the best of our knowledge, there are little data available for the effects of glycyrrhizin on the pharmacokinetics of paeoniflorin.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the glycyrrhizin, a triterpenoid saponin that isolated from liquorice, has anti-inflammatory, hepato-protective and antitumour properties. Some research articles have indicated that the drug-drug interaction might occur when they are coadministered (Hu et al 2003;Gao QT et al 2004;Chen et al 2012;Tai et al 2014;Feng et al 2015;Gao X et al 2016). To the best of our knowledge, there are little data available for the effects of glycyrrhizin on the pharmacokinetics of paeoniflorin.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the presence of verapamil, the oral bioavailability of Pristimerin is almost twice as high (1728.1 μg h/mL when given with verapamil vs. AUC0-t of 949.2 μg h/mL when given alone) in rats [12]. For these naturally occurring compounds, knowledge of toxicity or medicinal properties is usually earlier than an accurate understanding of the target or mechanism, and there is still a lot of knowledge about Pristimerin.…”
Section: Introductionmentioning
confidence: 99%